Umbrella repair of giant omphalocele, A new technique. - Mehran Hiradfar; Reza Shojaeian; Mahmoud Reza Ashab Yamin (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2017)
Introduction: Although many techniques have been described for reconstruction of the giant omphalocele, we present a simple , effective and safe new technique. Materials and Methods: We have studied 11 neonates with giant omphalocele that were treated by a new technique, Umbrella repair, in Sarvar pediatric hospital of Mashhad, Iran. In this new technique we released the skin around the omphalocele membrane just near the junction and a purse string suture is placed at the edge of the skin with beads beneath each bite and graded tightening of the suture in order to pushing the omphalocele toward the abdominal cavity. Finally we compare the results. Results: Among total 11 patients, mean age and weight at the time of operation were 2.18 days and 2150 grams respectively. comparing the results between groups, we observed significant less operative time and number of surgeries in neonatal period among patients who managed by umbrella repair. Post-operative complications, morbidity and mortality in umbrella repair group were also less than coventional methods. Conclusion: Umbrella repair provide a rapid and safe method for management of giant omphalocele with acceptable results and low morbidity and mortality.